2019
DOI: 10.1016/j.matbio.2018.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Defective lung function following influenza virus is due to prolonged, reversible hyaluronan synthesis

Abstract: Little is known about the impact of viral infections on lung matrix despite its important contribution to mechanical stability and structural support. The composition of matrix also indirectly controls inflammation by influencing cell adhesion, migration, survival, proliferation and differentiation. Hyaluronan is a significant component of the lung extracellular matrix and production and degradation must be carefully balanced. We have discovered an imbalance in hyaluronan production following resolution of a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
102
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(111 citation statements)
references
References 97 publications
3
102
0
6
Order By: Relevance
“…Although the nature of the clear jelly has yet to be determined, hyaluronan (HA) is associated with ARDS [12]; moreover, during SARS infection, the production and regulation of hyaluronan is defective. The levels of inflammatory cytokines (IL-1, TNF) are high in the lungs of COVID-19 patients and these cytokines are strong inducers of HA-synthase-2 (HAS2) in CD31 + endothelium, EpCAM + lung alveolar epithelial cells, and fibroblasts [13]. Importantly, HA has the ability to absorb water up to 1000 times its molecular weight.…”
Section: Hyaluronan: a Potential Cause Of Fatalitiesmentioning
confidence: 99%
“…Although the nature of the clear jelly has yet to be determined, hyaluronan (HA) is associated with ARDS [12]; moreover, during SARS infection, the production and regulation of hyaluronan is defective. The levels of inflammatory cytokines (IL-1, TNF) are high in the lungs of COVID-19 patients and these cytokines are strong inducers of HA-synthase-2 (HAS2) in CD31 + endothelium, EpCAM + lung alveolar epithelial cells, and fibroblasts [13]. Importantly, HA has the ability to absorb water up to 1000 times its molecular weight.…”
Section: Hyaluronan: a Potential Cause Of Fatalitiesmentioning
confidence: 99%
“…Stating that "hyaluronic acid is the most powerful water(edema)-binding substance in the body", they put forth a "humoral" and "biochemical-physiological" hypothesis of ARDS [9] . Others have recently detailed the central role of hyaluronic acid in human respiratory disease, in which viral infections lead to marked and rapid increase in hyaluronic acid concentrations [10]- [12] .…”
Section: Introductionmentioning
confidence: 99%
“…In the lung, the concentration of HA is elevated in the BALF of patients suffering from asthma ( 14 ), chronic obstructive pulmonary disease ( 48 ), interstitial pulmonary fibrosis ( 49 ), and other lung diseases [reviewed in ( 43 , 44 )]. In animal models, HA is upregulated in the bleomycin model of sterile injury ( 19 , 50 ), asthma (ova and cockroach allergen) ( 11 , 51 ), ozone-induced airway hyperreactivity ( 52 ), LPS-induced acute lung injury, and Escherichia coli ( 53 ), Klebsiella pneumoniae ( 54 ), or Influenza infection ( 55 ).…”
Section: Ha In the Inflamed Lungmentioning
confidence: 99%
“…During this recovery period, the lung is more susceptible to bacterial infections. Recent work found that HA levels remain high in the lung tissue due to elevated HAS2 expression in epithelial, endothelial, and fibroblast cells ( 55 ). TSG-6 levels are also elevated and this generates a HC-modified HA matrix ( 55 ).…”
Section: Ha In the Inflamed Lungmentioning
confidence: 99%
See 1 more Smart Citation